Pengaruh ROA, Current Ratio, Debt To Asset Ratio, Ukuran Perusahaan, Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Masa Pandemi Covid-19 (Studi Empiris Pada Perusahaan Sektor Property & Real Estate Yang Terdaftar di BEI Periode 2020-2021) - Idana Zulfa; Nurul Azizah (INTELLECTUAL CAPITAL, Jurnal Akuntansi Kontemporer, 2024)
This study shows to test the effect of Return On Asset (ROA), current ratio, Debt to Asset Ratio (DAR), company size, and investment decisions on company value during the Covid-19 pandemic. By using the population has been listed on the IDX, namely all property and real estate sector companies successively for the 2020-2021 period. Samples were selected while applying purposive sampling techniques through predetermined criteria and produced samples of 25 companies. In data analysis, multiple linear regression analysis was carried out using SPSS version 23. This study explains that the results during the Covid-19 pandemic Return On Asset (ROA), Debt to Asset Ratio (DAR), and company size have an influence on company value, but current ratios and investment decisions do not affect the company's value during the Covid-19 pandemic.